SUITABILITY ASSESSMENT OF GRETAGEOUS LIMESTONES FROM THERMO (AITOLOKARNANIA, WESTERN GREECE) FOR THEIR USE AS BASE AND SUB-BASE AGGREGATES IN ROAD-CONSTRUCTION - Mpalatsas, I.; Rigopoulos, I.; Tsikouras, Β.; Hatzipanagiotou, K. (Bulletin of the Geological Society of Greece, 2010)
This paper focuses on the assessment of mineralogical, petrographical and physico-mechanical properties of limestone formations in order to evaluate their suitability as road construction aggregates. Research focuses on Olonos-Pindos zone limestones of Creataceous age in Aitoloakarnania province, Western Greece. Special emphasis was given on comparing the mechanical properties to the mineral components. The results were evaluated in accordance with Greek and International suitability Standards for road construction aggregates. It was finally concluded that the physical and mechanical properties of the tested rocks are in compliance with the suitability Standards and that they can be used as road-construction aggregates.